(untitled) (مجلة الفاروق للعلوم, 2026)
The study was carried out to isolate and identify fungal genera associated with faba bean (Vicia faba L.) seeds. This study was conducted in the botany department of Life Sciences, Faculty of Arts and Sciences, Qasr Al-Akhyar. The results indicated that, five fungal genera: Aspergillus, Alternaria, Penicillium, Fusarium, and Rhizoctonia were detected among the non-surface-sterilized seeds; Aspergillus was the most commonly detected fungus in the samples (100%), followed by Alternaria (70%), Penicillium (60%), Fusarium (40%), and Rhizoctonia (30%). Aspergillus also displayed the greatest growth density, with an average of 3.9 CFU/plate, followed by Penicillium (2.4 CFU/plate), Alternaria (1.8 CFU/plate), Fusarium (1.1 CFU/plate), and Rhizoctonia (0.6 CFU/plate). Additionally, in the surface sterilization samples, the occurrence of all isolated fungi declined. However, Aspergillus remained the dominant genus, with a frequency of 50% and an average growth density of 1.3 CFU/plate. Alternaria revealed a higher frequency of occurrence than Penicillium. Whereas, Penicillium produced a greater growth density, displayed by a higher average colony count. In an other hand, Fusarium shows the lowest frequency (10%) and growth density (0.2 CFU/plate). The isolation of Aspergillus and Penicillium from both treatments suggests their strong association with faba bean seeds and their ability to persist on or within seed tissues. This finding is of particular importance because some species within these genera are known producers of mycotoxins, which may pose risks to seed quality as well as to human and animal health.